Rehabilitation Program for Spinal Cord Injury Neurological Level C2 due to Foramen Magnum Meningioma - Soracca Fellicita Sugiarto; Tanti Ajoe Kesoema (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Foramen magnum meningioma is a rare case. The incidence is 0.3% - 3.2% of all meningiomas. Clinical manifestations of foramen magnum meningioma are atypical and unpredictable. The main therapy for foramen magnum meningioma is surgery. The role of rehabilitation becomes important in the process after surgery. Case Presentation: A 46 years old female had weakness and loss of sensory of her upper and lower limbs, accompanied by urinary retention and constipation in the last 2 month, categorized by ASIAimpairment scale (AIS) C neurological level of injury at C2. Cervical MRI with contrast showed the impression of an extramedullary intradural mass as high as the inferior aspect of the pons to the corpusvertebrae cervical 1 supports the picture of meningiomas. The rehabilitation programs after surgery were active assistive range of motion exercise progressing to active range of motion, neuromuscular electrical stimulation, sensory stimulation and bladder and bowel training. Conclusion: The patient’s expectation for returning to independency is a long-term goal of the rehabilitation program. After definitive therapy (surgery) is conducted, medical rehabilitation management can be done as early as possible to achieve the optimum functional recovery. Muscle strengthening, sensory stimulation and bladder/bowel training improved motor , sensory and autonomic function.